FRACTIONS OF THE HEXANE EXTRACT OF YOUNG CARICA PAPAYA SEEDS CAN INHIBIT SPERMATOGENESIS IN MALE MICE MORE THAN FRACTION OF THE METHANOL EXTRACT OF YOUNG CARICA PAPAYA SEEDS - Satriyasa, Bagus Komang (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 2, No. 1 Maret 2008)
Fraction of hexane extract contains glycosides and triterpenoids, which isassumed to have an anti fertility ingredient, so it can be used as a male contraceptive,although the mechanism of action is not yet clear.This study used the pre-test and post-test control group design, using 30 malemice of balb C strain, aged 12 weeks, weight 20-22 gram, subsequently grouped byrandom into 3 groups each consisting of 10 male mice. One control group (P0 = controlgroup) was given double distilled water, and two treatment groups (P1 = treatment group)was given fraction of the hexane extract of young Carica papaya seed 20 mg/20gram/day,P2 = treatment group) was given fraction of the methanol extract of young Carica papayaseed 20 mg/20 gram/day). After 36 days of treatment, evaluation of the testis and blood,of the male mice was conducted.Data were analysed by normality test of Kolmogorov Smirnov Goodness of Fit,homogeneity test, and Anova test. This study showed that cells of spermatogonia A,primary pakhiten spermatocyte, spermatid, and Sertoli cells, decreased significantly (p <0,05) but Leydig cells and testosterone were not decreased significantly (p > 0,05).It is concluded that fraction of hexane extract of carica papaya seeds can decreasethe mean number of cells spermatogonia A, spermatocyte of primary pakhiten, spermatid,Sertoli, and Leydig cells and the level of testosterone hormone better than fraction ofmethanol extract of young Carica papaya seeds.
Keywords: Spermatogenesis, testosterone, fraction hexane extract of young Carica papaya seeds and fraction methanol extract of young Carica papaya seeds, male mice.